Valproic Acid For Refractory Post-Traumatic Dizziness and Photopsia - Graviela Kosuhary; Azmi Farah Fairuzya; Stephen Changifer (Lumina : Indonesian Journal of Neurology, 2025)
Introduction: Post-concussion syndrome (PCS) is a collection of cognitive, vestibular, and visual symptoms that may persist after mild traumatic brain injury (mTBI). Current management is largely supportive, highlighting the need for alternative pharmacologic approaches. This case report explores the therapeutic potential of valproic acid (VPA), a compound with neuroprotective and anti-inflammatory effects.Case Presentation: A 28-year-old woman presented with persistent vertigo and visual disturbances, including photopsia, following a mild head injury sustained in a motor vehicle accident. Neurological examination and imaging were unremarkable. Symptomatic therapies provided only partial and temporary relief, prompting the trial of VPA. The patient subsequently experienced gradual clinical improvement, achieving complete symptom resolution within six months and maintaining remission after discontinuation of treatment.Discussion: The patient’s symptoms were attributed to functional disturbances involving the occipital cortex and vestibular pathways, commonly implicated in PCS. Hypothesized contributors included ionic disequilibrium, cortical hyperexcitability, and neuroinflammatory processes. Beyond its traditional use as an antiepileptic, VPA may offer therapeutic advantages in PCS through GABAergic modulation, Histone Deacetylase (HDAC) inhibition, and anti-inflammatory actions.Conclusions: This case highlights VPA as a promising pharmacologic option for refractory PCS. However, further studies are required to determine its efficacy, optimal dosage, and safety profile in this setting.Keywords: Post-Concussion Syndrome; Valproic Acid; Mild Traumatic Brain Injury; Vestibular Symptoms; Visual Dysfunction